Structural and spectroscopic properties of some neodymium-boro-germanate glasses and glass ceramics embedded with silver nanoparticles. Issue 15 (15th October 2017) - Bolundut, Liviu; Pop, Lidia; Bosca, Maria; Borodi, Gheorghe; Olar, Loredana; Suciu, Ramona-Crina; Pascuta, Petru; Culea, Eugen; Stefan, Razvan
Abstract: Neodymium-boro-germanate glasses and glass ceramics (with Nd2 O3 contents up to 40 mol%) embedded with silver metallic nanoparticles (AgNPs) were prepared by the melt-quenching technique. Two series of samples (with AgNPs and without AgNPs) were investigated by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, diffuse reflectance ultraviolet–visible (DR-UV–vis) spectroscopy and photoluminescence (PL) spectroscopy. XRD data reveal that for both series the samples with x < 40 mol% Nd2 O3 are basically amorphous containing only small amounts of a crystalline phase (identified as crystalline B2 O3 ) while for samples x = 40 mol% Nd2 O3 an important amount of a crystalline phase (identified as the NdBO3 orthorhombic phase) is present. FT-IR spectroscopy data show that addition of controlled amounts of Nd2 O3 and AgNPs changes the structural units that build up the host glass ceramic network. These changes were confirmed also by the photoluminescence spectra that show that addition of AgNPs to the host matrix produces changes at the level of emission peaks. The positive values of bonding parameter (δ) calculated based on DR-UV–vis data indicate a covalent character of the bonds from the studied samples.